Horizontal gene transfer from Agrobacterium to plants - Matveeva, Tatiana V.; Lutova, Ludmila A. (Frontiers in Plant Science, 2014)
Most genetic engineering of plants uses Agrobacterium mediated transformation to introduce novel gene content. In nature, insertion of T-DNA in the plant genome and its subsequent transfer via sexual reproduction has been shown in several species in the genera Nicotiana and Linaria. In these natural examples of horizontal gene transfer from Agrobacterium to plants, the T-DNA donor is assumed to be a mikimopine strain of A.rhizogenes. A sequence homologous to the T-DNA of the Ri plasmid of Agrobacterium rhizogenes was found in the genome of untransformed Nicotiana glauca about 30 years ago, and was named “cellular T-DNA” (cT-DNA). It represents an imperfect inverted repeat and contains homologues of several T-DNA oncogenes (NgrolB, NgrolC, NgORF13, NgORF14) and an opine synthesis gene (Ngmis). A similar cT-DNA has also been found in other species of the genus Nicotiana. These presumably ancient homologues of T-DNA genes are still expressed, indicating that they may play a role in the evolution of these plants. Recently T-DNA has been detected and characterized in Linaria vulgaris and L. dalmatica. In Linaria vulgaris the cT-DNA is present in two copies and organized as a tandem imperfect direct repeat, containing LvORF2, LvORF3, LvORF8, LvrolA, LvrolB, LvrolC, LvORF13, LvORF14, and the Lvmis genes. All L. vulgaris and L. dalmatica plants screened contained the same T-DNA oncogenes and the mis gene. Evidence suggests that there were several independent T-DNA integration events into the genomes of these plant genera. We speculate that ancient plants transformed by A. rhizogenes might have acquired a selective advantage in competition with the parental species. Thus, the events of T-DNA insertion in the plant genome might have affected their evolution, resulting in the creation of new plant species. In this review we focus on the structure and functions of cT-DNA in Linaria and Nicotiana and discuss their possible evolutionary role.